2011
DOI: 10.1155/2011/645030
|View full text |Cite
|
Sign up to set email alerts
|

Contemporary Radical Prostatectomy

Abstract: Purpose. Patients diagnosed with clinically localized prostate cancer have more surgical treatment options than in the past. This paper focuses on the procedures' oncological or functional outcomes and perioperative morbidities of radical retropubic prostatectomy, radical perineal prostatectomy, and robotic-assisted laparoscopic radical prostatectomy. Materials and Methods. A MEDLINE/PubMed search of the literature on radical prostatectomy and other new management options was performed. Results. Compared to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 128 publications
(118 reference statements)
0
23
0
Order By: Relevance
“…Prostate cancer (PC) is one of the most common malignancies in men in Europe and the United States . Local PC is potentially curable with radiation therapy, hormone therapy, and/or radical prostectomy . However, up to 40% of the patients who are diagnosed with localized disease ultimately develop advanced PC, even after initial treatment of local disease .…”
Section: Prostate Cancermentioning
confidence: 99%
“…Prostate cancer (PC) is one of the most common malignancies in men in Europe and the United States . Local PC is potentially curable with radiation therapy, hormone therapy, and/or radical prostectomy . However, up to 40% of the patients who are diagnosed with localized disease ultimately develop advanced PC, even after initial treatment of local disease .…”
Section: Prostate Cancermentioning
confidence: 99%
“…Although robotic assisted radical prostatectomy is being most commonly performed in developed countries but as for as the trifecta of the surgery is concerned robotic as well as the RPP techniques have yielded equivalent effectiveness rates of functional, oncological, and surgical outcomes [14]. Infact many studies have shown RPP as a minimally invasive procedure that was found to be the most costeffective [15,16,17,18]. Success of open radical prostatectomy has improved with clear understanding of periprostatic anatomy.…”
Section: Discussionmentioning
confidence: 99%
“…The same indications apply to retropubic (RRP), laparoscopic (LRP), and robot-assisted radical prostatectomies (RARP), all of which can be categorized into one coherent “retropubic complex”, and radical perineal prostatectomy (RPP) as a distinct kind of procedure [ 3 , 4 , 8 , 14 ]. The differences among these procedures reside in the access to the prostate, as all procedures result the same with no significant superiority [ 3 , 8 , 12 , 14 20 ]. The current trend towards ‘minimalism’, however, should not challenge the principles of radical prostatectomy.…”
Section: Discussionmentioning
confidence: 99%